English for specific purposes (Teachers of English to Speakers of Other Languages, Inc., 2002)
English for Specific Purposes (ESP) is an exciting movement in language education. It is opening up rich opportunities for English teachers and researchers in new professional domains. Whatever one's teaching context, these case studies offer much to learn about curriculum and course planning, implementation, and evaluation.